2018
DOI: 10.1007/s11284-018-1585-1
|View full text |Cite
|
Sign up to set email alerts
|

Relative ascendency predicts food web robustness

Abstract: Threats to ecosystems globally from anthropogenic disturbance and climate change requires us to urgently identify the most sensitive biological communities to ensure they are effectively preserved. It is for this reason that understanding and predicting food web stability has been topical within ecology. Food web stability is a multi‐faceted concept that represents the ability of a food web to maintain its integrity following disturbance, it includes resistance, resilience and fragility. In this study, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…It is plausible that when DIN concentrations exceed 0.55 mg/L that hypoxic events occur and disturb the system sufficiently to drop relative ascendency. Ulanowicz (1997b) found that most weighted food webs have very similar relative ascendency values, which has been suggested to represent a common trade‐off between adaptable yet inefficient communities and efficient yet brittle communities—termed the window of vitality (Canning & Death, 2018; Ulanowicz, 2009; Ulanowicz et al., 2009). Interestingly, all the webs we assessed were within the window of vitality, with the webs of highest relative ascendency occurring approximately at the upper boundary of the established window.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is plausible that when DIN concentrations exceed 0.55 mg/L that hypoxic events occur and disturb the system sufficiently to drop relative ascendency. Ulanowicz (1997b) found that most weighted food webs have very similar relative ascendency values, which has been suggested to represent a common trade‐off between adaptable yet inefficient communities and efficient yet brittle communities—termed the window of vitality (Canning & Death, 2018; Ulanowicz, 2009; Ulanowicz et al., 2009). Interestingly, all the webs we assessed were within the window of vitality, with the webs of highest relative ascendency occurring approximately at the upper boundary of the established window.…”
Section: Discussionmentioning
confidence: 99%
“…and efficient yet brittle communities-termed the window of vitality (Canning & Death, 2018;Ulanowicz, 2009;Ulanowicz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ascendency is a measure of the average mutual information in a system. That is, Ascendency is a measure of the amount of specialist pathways and the size of a food web (Canning and Death, 2018). Ascendancy is inversely proportional to the uncertainty of where a unit of energy will flow next in a food web.…”
Section: Ascendencymentioning
confidence: 99%